Fraud Diamond Dalam Pendeteksian Kecurangan Laporan Keuangan Pada Perusahaan BUMN - Kristianti, Indah (Universitas 17 Agustus 1945 Jakarta, 2025)
This study aims to examine the effect of the Fraud Diamond using four proxies, namely financial targets, ineffective monitoring, auditor turnover, and director turnover, on financial statement fraud in BUMN during the 2023–2024 period. The population consists of 126 BUMN, with 35 of them listed on the Indonesia Stock Exchange (IDX). A sample of 13 companies was selected using purposive sampling based on predetermined criteria. Secondary data in the form of financial statements and annual reports from the sampled companies over two years were analyzed, totaling 26 observations. Multiple regression analysis was performed using E-Views 12 software. The results show that financial targets have a significant negative effect on financial statement fraud, ineffective monitoring and auditor turnover have no significant effect, while director turnover has a significant positive effect.